2022
DOI: 10.1136/jitc-2022-004579
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic CD69+Vδ1 T cells re-circulate in the blood of patients with metastatic colorectal cancer and limit tumor progression

Abstract: BackgroundMore than 50% of all patients with colorectal cancer (CRC) develop liver metastases (CLM), a clinical condition characterized by poor prognosis and lack of reliable prognostic markers. Vδ1 cells are a subset of tissue-resident gamma delta (γδ) T lymphocytes endowed with a broad array of antitumor functions and showing a natural high tropism for the liver. However, little is known about their impact in the clinical outcomes of CLM.MethodsWe isolated human γδ T cells from peripheral blood (PB) and peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…The relationship between gd T cells and cancer prognosis is influenced by factors such as the pathological type of cancer (31), the gd T-cell subset (32), the time of sample harvesting (33), and the functioning state of the gd T cells (34). Clinical prognosis studies typically involve the analysis of either peripheral gd T cells or tumor-infiltrating gd T cells, and common methods include flow cytometry (35), immunohistochemistry (31,36), and gene expression measurement (34,37). Early studies often measured peripheral gd T cells without distinguishing subsets (38), whereas later studies began to analyze subsets separately (35).…”
Section: Gd T Cells In Cancer 21 Correlation With Clinical Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between gd T cells and cancer prognosis is influenced by factors such as the pathological type of cancer (31), the gd T-cell subset (32), the time of sample harvesting (33), and the functioning state of the gd T cells (34). Clinical prognosis studies typically involve the analysis of either peripheral gd T cells or tumor-infiltrating gd T cells, and common methods include flow cytometry (35), immunohistochemistry (31,36), and gene expression measurement (34,37). Early studies often measured peripheral gd T cells without distinguishing subsets (38), whereas later studies began to analyze subsets separately (35).…”
Section: Gd T Cells In Cancer 21 Correlation With Clinical Prognosismentioning
confidence: 99%
“…As most studies on solid tumors have focused on tumor-infiltrating cells, the majority of correlations between prognosis and gd T cells have been found in tumor-infiltrating cells. Effector Vd1 gd T cells have been found to be beneficial in skin cancers (32,48), colon cancer (34), and lung cancer (35), based on protein-level analysis. Similarly, using the more commonly used gene expression analysis, tumor-infiltrating gd T cells were found to be favorable in ovarian cancer (49), head and neck cancer (50), and bladder cancer (37).…”
Section: Gd T Cells In Cancer 21 Correlation With Clinical Prognosismentioning
confidence: 99%
“…High levels of γδT cells were positively correlated with clinical stage, overall survival (OS) time, and CD8+/CD4+ T-cell infiltration [ 45 ]. In metastatic colorectal cancer, γδT cells still show the ability to limit tumor progression [ 5 ]. By analyzing 25 kinds of cancers (other than brain cancers), it was found that a tumor-related γδT-cell gene signature was the factor most correlated with the OS rate of patients [ 46 ].…”
Section: Interaction Between the Tme And γδT Cellsmentioning
confidence: 99%
“…In recent years, many studies have shown that cytotoxic γδT cells have a strong killing ability toward autologous, allogeneic or xenogeneic tumor cells, and their concentration is often closely related to the clinical prognosis of patients [ 1 5 ]. In contrast to αβT cells, γδT cells can recognize antigens in a way that is not restricted by major histocompatibility complex (MHC) molecules [ 6 ], and they mediate the killing of target cells in various ways, participate in immunomodulation, and have a broader tumor cell killing spectrum [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vδ3 T cells are enriched in the liver and in patients with some chronic viral infections and leukemias. They bind to glycolipid antigens presented by the MHC class I-like molecule CD1d and annexin A2 [15][16][17][18]. Other human γδ T cell subsets, such as Vδ4, Vδ5, Vδ6, Vδ7, and Vδ8 T cells, have been mainly found in patients with pathological conditions [19,20].…”
Section: Introductionmentioning
confidence: 99%